Hubungan Pengetahuan Dan Sikap Ibu Hamil Tentang Ketuban Pecah Dini Dengan Perilaku Pencegahan Ketuban Pecah Dini Di Wilayah Kerja Uptd Puskesmas Tanjung Harapan - Klara Vamiga Permata Mahardika; Berlian Kando Sianipar; Ravika Ramlis (Jurnal Multidisiplin Dehasen (MUDE), 2026)
Premature rupture of the membranes (PROM) is the rupture of the amniotic sac before labor. This study aims to determine the correlation between pregnant women's knowledge and attitudes about premature rupture of membranes and their preventive behavior in the Working Area of UPTD Tanjung Harapan Health Center. This quantitative, cross-sectional study was conducted in Tanjung Harapan Health Center, Ulok Kupai Sub-District, North Bengkulu Regency, from July 1 to 30, 2025, with a sample size of 43 respondents. Data collection used a research questionnaire. The results showed that respondents with sufficient knowledge had good behavior (51.16%), while those with low knowledge were evenly distributed between those with good and poor behavior (2.33% each). Respondents with positive attitudes tended to have good behavior (41.86%), while respondents with negative attitudes had good behavior (25.58%). A P-value of 0.035 indicates a statistically significant correlation between knowledge and attitudes toward behavior (since P < 0.05). The researchers recommend that Health Centers implement guidance, coaching, and counseling programs regarding the relationship between knowledge and attitudes of pregnant women and behaviors related to premature rupture of membranes.